Optimization of Fractional Order PID Controller Using Grey Wolf Optimizer - Verma S.K.; Yadav S.; Nagar S.K. (My University, 2025)
This paper presents a novel evolutionary technique to optimize the parameters of fractional order controller for controlling two classes of systems: time-delay and higher-order system. The evolutionary technique known as grey wolf optimizer is used to tune both integer and fractional order controllers. The grey wolf optimizer searches for the optimum solution in the following manner, i.e. encircling, hunting, attacking the prey and finally search for the new prey consecutively if exists. To certify these various procedure, the performance indices like integral square error, integral absolute error, integral time-weighted square error, and integral time-weighted absolute error are minimized for the authenticity. Moreover, the proposed algorithm is validated and compared with well-established techniques. © 2017, Brazilian Society for Automatics--SBA.